Features of the Structural Elements of the Linguistic Worldview in Teaching the Russian Language - Tasheva Dilorom Salimovna; Vafaeva Zamira Giyasovna (Genius Journals, 2022)
Linguistic knowledge serves as the basis for the formation of student's language and speech skills. No skill can be formed without relying on knowledge. With acquaintance with them, the development of skills begins, therefore, linguistic concepts should be included in the university curriculum. This article discusses the features of the structural elements of the linguistic worldview in teaching the Russian language and how to be successful in educational process giving students all necessary skills.
Keywords: Language development; systematic language; phonetics; vocabulary